Specifics of the Calendar Rituals of Ethnic Romanians of Bessarabia - Sokolova, Alla (Journal of Danubian Studies and Research, 2023)
The article examines the calendar rituals of ethnic Romanians of Bessarabia, since it is folk festivals, customs and rituals, as components of traditional culture, that reflect the national characteristics of the Romanian community, characterizing it as an ethnically distinctive organization. The purpose of the study is to reconstruct the complex of calendar rituals of ethnic Romanians of southern Bessarabia, to identify its internal structure and content in the system of traditional culture, and to clarify its local specifics. To achieve this aim, it is necessary to solve the following tasks: to outline the place and role of calendar rituals in the traditional ethnic culture of the inhabitants of Bessarabia and to characterize folk holidays, customs, and rituals of the calendar cycle. The use of the field research method (survey, questionnaire, individual interview, direct observation) allowed us to determine the specifics of the traditional culture of ethnic Romanians of Bessarabia, to identify common features of Romanian calendar rituals in the context of the ethno-cultural landscape of the Bessarabian region. The study of the ritual poetry of the Romanian ethnic group of the Ukrainian Danube region has shown that the entire annual cycle of folk rituals and holidays is consistent with the seasons of the folk calendar. A detailed study of rituals, customs, and folk holidays as an important component of traditional Romanian culture made it possible to consider the calendar ritualism in a complex and to trace the connection between the Slavic and Romanic layers of folk ritualism of the calendar cycle in both historical and functional aspects.